ANALISIS PENGEMBANGAN KAPASITAS DESA WISATA BURAI KABUPATEN OGAN ILIR MENUJU PARIWISATA BERKELANJUTAN - Mira Shintia (STKIP Subang, 2025)
This study analyzes the development of Burai Village in Ogan Ilir Regency as a creative tourism village through the innovation of the Colorful Village. The study uses the capacity building framework of Grindle (1997) at the system, organization, and individual levels, with a descriptive qualitative method through literature studies, observations, and documentation. The results show that the development process takes place through six stages, namely community-based planning, the development of facilities and infrastructure, as well as the strengthening of local institutions such as Pokdarwis and BUMDes, supervision by the government and the community, digital promotion through social media, education and training of tourism managers, and strengthening regulations through Regent Decree Number 457 of 2021. These findings confirm that the success of Burai Village is not only supported by tourist attractions, but also by building the capacity of the community, organizations, and sustainable government policy support.